Concerning children / by Charlotte Perkins (Stetson) Gilman. - Gilman, Charlotte Perkins, 1860-1935. (Tufts University. Tisch Library., 2016)
1 online resource (95 pages).; "Issued for the Rationalist Press Association, Limited, by arrangement with Messrs. G.P. Putnam's Sons."; Tisch In-House Digitization 2016-02-22